2011
DOI: 10.1002/cncr.26300
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term postsurgical prognosis of patients with pineoblastoma

Abstract: BACKGROUND: For this report, the authors comprehensively summarized the existing literature on patients with pineoblastoma and identified the variables and treatments that had an impact patient on outcomes. METHODS: A comprehensive search identified 109 studies that collectively described the outcomes of patients with pineoblastoma. Individual patient data were classified based on treatment and were subjected to univariate comparisons. Cox regression analysis included comparisons of survival outcomes controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 65 publications
10
71
2
Order By: Relevance
“…Although they typically appear radiographically as a focal enhancing mass, pineoblastomas can be locally invasive and spread outside the pineal region through the subarachnoid space. Pineoblastomas are more common in children than in adults and adults account for <10% of patients [1]. …”
Section: Discussionmentioning
confidence: 99%
“…Although they typically appear radiographically as a focal enhancing mass, pineoblastomas can be locally invasive and spread outside the pineal region through the subarachnoid space. Pineoblastomas are more common in children than in adults and adults account for <10% of patients [1]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that GTR may play a vital role in the treatment of PB (15,16). However, despite significant improvements in surgical techniques and perioperative care, a high risk is associated with surgical intervention in the pineal area owing to its proximity to critical structures.…”
Section: A B C D E F G Hmentioning
confidence: 99%
“…Although craniospinal irradiation has been shown to prevent leptomeningeal recurrence, pineoblastomas are known to have a poor prognosis. 1 Pineoblastomas tend to recur on the surfaces of the neural tissue rather than in the parenchyma and all the lesions identified in the patient were far from the pineal gland, although there are case reports of brain metastasis related to the manipulation of a pineoblastoma after stereotactic or endoscopic biopsy. 2 In this case, tumor recurrence was considered after the first MRI showing white matter changes, but the subsequent improvement without specific treatment is not expected in a malignant condition.…”
Section: Sectionmentioning
confidence: 95%